Innovative Mosque Management: Transforming Social Services and Youth Engagement at Masjid Sejuta Pemuda in Sukabumi, Indonesia - Widiawati, Wiwin; M. Yusuf Wibisono; Busro (Tashwirul Afkar, 2025)
This research aims to systematically explore the religious social service programmes at the Masjid Sejuta Pemuda, focusing on the management structure, implementation of ongoing social programmes, and identification and evaluation of their impact on the community. This research is important because it provides an understanding of inclusive, sustainable, and data-based mosque management practices. The method used is qualitative with a sociology of religion approach. Data collection techniques include interviews, observation, and document analysis, while analysis is done thematically through the stages of data reduction, data presentation, and conclusion drawing. The results showed that Masjid Sejuta Pemuda succeeded in developing a sustainable modern mosque management model through five main pillars, namely worship, education, social, economic, and ukhuwah. Flagship programmes such as Musafir Friendly Mosque, Dapur Bagi-Bagi, and Free Premium Coffee Bar demonstrate the application of social mapping and a targeted data-based approach. Financial transparency and digitalisation of administration also strengthen management effectiveness. As a result, the mosque is able to increase youth participation, strengthen social solidarity, and provide economic and spiritual benefits to the surrounding community. The findings have important implications for the development of more innovative and independent mosque management, and can be replicated as a model for modern mosques. In an original way, this research offers a new contribution to the mosque management literature through the concept of ‘Mosque of Civilization 5.0’ that integrates social services, technology, and youth leadership. The research also provides practical guidance for mosque managers in implementing social innovation, youth recruitment strategies, digital fundraising, and transparent financial management.